Efficacy, Treatment Characteristics, and Biopsychological Mechanisms of Music-Listening Interventions in Reducing Pain (MINTREP): Study Protocol of a Three-Armed Pilot Randomized Controlled Trial - Feneberg, Anja C.; Kappert, Mattes B.; Maidhof, Rosa M.; Doering, Bettina K.; Olbrich, Dieter; Nater, Urs M. (Frontiers in Psychiatry, 2020)
Background: Pain can severely compromise a person’s overall health and well-being. Music-listening interventions have been shown to alleviate pain and to modulate the body’s stress-sensitive systems. Despite the growing evidence of pain- and stress-reducing effects of music-listening interventions from experimental and clinical research, current findings on music-induced analgesia are inconclusive regarding the role of specific treatment characteristics, underlying biopsychological mechanisms, and the stability of these effects. Objective: The overall aim of this pilot randomized controlled trial is to test and compare the differential effects of frequency-modulated and unmodulated music (both researcher-selected) on experimentally induced pain and to test the efficacy of the interventions in reducing subjective and biological stress levels. Moreover, these two interventions will be compared to a third condition, in which participants listen to self-selected unmodulated music. Methods and analysis: A total of 90 healthy participants will be randomly allocated to one of the three music-listening intervention groups. Each intervention encompasses ten sessions of music listening in our laboratory. Pain will be induced via the cold pressor test. Primary (i.e., pain intensity, pain tolerance) and secondary (i.e., heart rate variability, electrodermal activity, hair cortisol, subjective stress) outcomes will be measured at baseline, post, and follow-up as well as intermittently. In addition, a range of tertiary health-related parameters will be assessed. Discussion: This is the first study to systematically test and compare the effects of music frequencies along with the control over music selection, both of which qualify as central treatment characteristics of music-listening interventions. This study permits to elucidate the potential biopsychological mechanisms underlying music-induced analgesia and to explore the scope, stability- and the dose-response relationship of the interventions. Results will be highly informative for the design of subsequent large-scale clinical trials and provide valuable conclusions for the implementation of music-listening interventions for pain relief. Ethics and dissemination: The study has been approved by the local ethics committees at the Philipps-University Marburg and at the University of Vienna. Results of this study will be presented at conferences and submitted for publication in peer-reviewed journals. Trial registration: Clinical Trials Database of the U.S. National Library of Medicine: Identifier NCT02991014.